Charpy Impact Value of Friction Stir Welded 7020 and 7075 Aluminium Alloys at Different Tool Rotation and Transverse Speed - Shawnim R. jalal (Engineering and Technology Journal, 2010)
In this work, the effect of friction stir welding parameters such as tool rotation and tool transverse speed on the impact value of 7mm thick weldments of aluminum alloys 7020 and 7075 each alone at T6 and T9 temper conditions has been studied and investigated. Three tool rotation speed (280, 580, and 960 rpm) and five tool transverse speed (36, 76, 102, 146, and 216mm/min) were selected for the friction stir welding of each alloy condition. The resistance of weldments tosudden loading has been investigated using the Charpy impact test with standard V– notched specimens at room temperature. It has been observed during this work that the total impact energy increased in the friction stir welding of (medium strength) 7020 Al alloy for both temper conditions especially at 580 rpm and 102 mm/min with respect to the base metal while rotation and transverse speed have little effect on the impact value of (high strength) 7075 Al alloy and the results were very close to each other. Finally it is important to mention that the relationbetween rotation speed, transverse speed and input heat which affect on the impact value seems to be complex and depend on the material properties being welded.